Grandcamp w skali mikro. O Na skałach Calvados Antoniego Sygietyńskiego - Janiak-Staszek, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This study contains the micrological quest for proposals of new interpretation of the novel by Antoni Sygietyński entitled "Na skałach Calvados". The starting point for the discussion is the love for detail instilled in Sygietyński by Gustave Flaubert. The details, which have been omitted by the literature researchers so far, seem to be the key to decoding the characters‘ conduct, one which is consciously and consistently used. It is the space of the home that is the centre of these signs. A significant role in the novel is also played by the red colour. These trails lead to discovering the secrets of Sygietyński's writing technique.